Mapping and Revitalization of the Libraries of Santa Catarina and San Pedro Garza García in Nuevo León, Mexico - Sindy Melissa Godínez De León; América Desirée Fraire Ramírez (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Libraries' architecture is fundamental in shaping a community's knowledge and culture. Their design, when thoughtful, has a significant impact on creating dynamic environments spread across cities and optimizes the functionality of the space, contributing to the creation of informed, connected, and culturally enriched communities. Adapting libraries to modern needs and using technologies that are easy to navigate are priorities in Mexico. The impact of evolving educational and research spaces can allow future generations access to the richness of knowledge accumulated over time, fostering local engagement. With the ease of getting lost in the routine of today's accelerated life, changing a community's vision can be challenging. Still, reactivating libraries through their architecture can reshape the community's lifestyles. This article aims to show the mapping process, the analysis, and the comparison libraries in Mexico's Santa Catarina and San Pedro Garza García to establish a spatial proposal regarding the enrichment libraries provide to the surrounding communities.